Efektivitas Pemberian Alokasi Kamar pada Biro Perjalanan Wisata: Kasus di Hotel The Kuta Beach Heritage Bali - Danny Martin; Ida Ayu Sri Puspa Adi; Putu Ayu Ariasih (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2021)
Despite the rapid development of online travel agents who market hotel rooms via the internet, traditional travel agencies also still play an important role in marketing and booking hotel rooms. As The Kuta Beach Heritage hotel still utilizes and uses room marketing channels through offline travel agencies. This study aims to determine the effectiveness of providing room allocation or room allocation to travel agents at The Kuta Beach Heritage Bali. The data used is secondary data in the form of production from each travel agency and given room allocation. While the primary data was obtained through interviews with various related parties at the hotel. Data were analysed quantitatively and qualitatively. The results showed that the utilization of room allocation by the travel agency had not been maximized or had not been able to achieve the target given by the hotel, which was 60%. The practical implication of this research is the need for innovative efforts to increase the production of room nights by both hotels and travel agencies